2014
DOI: 10.1016/j.stemcr.2014.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Generation of Universal Platelets from Human Induced Pluripotent Stem Cells

Abstract: SummaryHuman induced pluripotent stem cells (iPSCs) provide a potentially replenishable source for the production of transfusable platelets. Here, we describe a method to generate megakaryocytes (MKs) and functional platelets from iPSCs in a scalable manner under serum/feeder-free conditions. The method also permits the cryopreservation of MK progenitors, enabling a rapid “surge” capacity when large numbers of platelets are needed. Ultrastructural/morphological analyses show no major differences between iPSC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
315
0
17

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(342 citation statements)
references
References 46 publications
10
315
0
17
Order By: Relevance
“…Based on our studies, we believe that RNAi might be a superior tool to reduce the immunogenicity of iPSC-derived cell products because silencing HLA to upregulate CD62P and to aggregate. These results are in concordance with previous studies, which have shown that iPSC-derived HLA-expressing PLTs are functional (9,39 (B) The graph shows mean and SD of the PLT frequencies detected after HLA-universal MK transfusion in three independent experiments. **p ≤ 0.01.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Based on our studies, we believe that RNAi might be a superior tool to reduce the immunogenicity of iPSC-derived cell products because silencing HLA to upregulate CD62P and to aggregate. These results are in concordance with previous studies, which have shown that iPSC-derived HLA-expressing PLTs are functional (9,39 (B) The graph shows mean and SD of the PLT frequencies detected after HLA-universal MK transfusion in three independent experiments. **p ≤ 0.01.…”
Section: Resultssupporting
confidence: 91%
“…Despite some attempts for the establishment of iPSC haplobanks to cover the most frequent HLA haplotypes, it is known from the field of transplantation that even HLA-matched grafts can be rejected due to the presentation of polymorphic mHAs (13,14). Recently, the concept of generating HLA-universal PLTs has been developed using different tools such as RNA interference (RNAi) or Clustered Regularly Interspaced Short Palindromic Repeats/Cas9 (CRISPR/Cas9) (9,10). Previously, we have demonstrated that silencing HLA expression using RNAi prevents an allogeneic immune response in vitro and in vivo.…”
Section: Generation Of Mks and Plts From Hla-universal Ipscsmentioning
confidence: 99%
See 2 more Smart Citations
“…An attractive feature of platelets derived from stem cell culture is the prospect of genetically manipulating progenitor cells to generate platelets devoid of HLA antigens. 12 This would eliminate the risk of alloimmunization against HLA class I antigens and the resulting refractoriness to subsequent platelet transfusions, which is still a serious clinical problem. Clearly, further progress must be made for this platelet source to become a clinical reality.…”
mentioning
confidence: 99%